Chemical Biosensors Based on Proteins Involved in Biomineralization Processes - Ruiz-Arellano, Rayana R.; Serrano-Posada, Hugo Javier; Marín-García, Maria Liliana; Frontana-Uribe, Bernardo A.; Moreno, Abel (IntechOpen, 2011)
None